ALANG “LUMBUNG PADI” DAN STATUS SOSIAL PADA MASYARAKAT TORAJA DI LEMBANG BENTENG KA’DO - Merianti Tampang; Veronika E.T Salem; Hamdi Gugule (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2020)
The purpose of this study was to determine the public perception of the social status of Alang owners in Toraja society and to determine the function of Alang in Toraja society. The problem in this research is the public perception of the social status of the owner of the Lumbung Padi Alang in the Toraja community. The research method used is qualitative research. The research method that aims to provide a systematic, factual and accurate description. By using library research data collection techniques, field research and documentation. The results in the field show that the Alang Culture and Social Status in the Toraja people are still maintained. One of them is Alang "Lumbung Padi", in this case the meaning of Alang from year to year remains the same, namely Tongkonan which is called Mother and Alang is called the Father besides that it is also a complement to the Tongkonan house. And for the public's perception of the status of the owner of a rice barn, namely that not only people with aristocratic caste can have "Alang" but even people with lower caste can own it only depending on their abilities.